Undertreatment of Pain in HIV+ Adults in Thailand - Robbins N.M. (2014)
Context: Chronic pain remains prevalent in HIV+ adults despite widespread antiretroviral use. Pain continues to be underrecognized and undertreated in this population. In Thailand, similar to the West, HIV care is transitioning toward chronic disease management. Despite the importance of pain management in chronic HIV, the prevalence of pain and adequacy of pain management is unknown in HIV+ adults in Thailand. Objectives: This cross-sectional study aimed to determine the prevalence of chronic pain, the burden of inadequate analgesia, and risk factors for chronic pain in HIV+ adults in Thailand. Methods: A total of 254 HIV+ adults were recruited from an outpatient clinic in Thailand. Interviewers obtained information on demographics, clinical data, and pain characteristics. The burden of inadequate analgesia was assessed using the Brief Pain Inventory. Risk factors were identified with logistic regression analysis. Results: Frequent pain was reported by 27% of participants; 22% reported chronic pain. Pain was significantly associated with education less than primary school, a positive depression screen, and the number of years on combined antiretroviral therapy. Eighty-six percent of patients with frequent pain were inadequately treated. Of 34 patients with moderate or severe pain, none received adequate analgesia. Inadequate analgesia was a significant risk factor for poorer quality of life. Conclusion: Despite widespread antiretroviral use, pain remains common and undertreated in HIV+ adults in Thailand. Undertreated pain negatively impacts quality of life. It is imperative that policy makers and HIV caregivers address this treatment gap to advance the care of people living with HIV in Thailand. © 2013 U.S. Cancer Pain Relief Committee.